“Rechazado como regalo, recibido como préstamo”: el fraude a la ley y los Rolex de la presidenta - Mendoza del Maestro, Gilberto (2024)
In this article, the authors analyze the events that involve the current president of the nation, Dina Boluarte, and the scandal related to the Rolex watches she wore on different occasions. Although this controversial case is initially approached from a civil perspective, the authors realize that other branches of Law, such as Criminal Law, would also be applicable.